Prediction of Ozone Pollution through Chaotic Approach - Zila Abd Hamid, Nor (International Journal of Engineering and Technology, 2018)
This study is about applying chaotic approach in analyzing and predicting ozone (O3) pollution. There are two stages in chaotic approach. The first is to detect the presence of chaotic nature by means of phase space plot and Cao method while the second stage is the prediction through the local mean approximation method. Result found that O3 pollution recorded at one of Malaysian leading educational university namely Sultan Idris Education University is detected as chaotic in nature. Thus, the prediction is continued using chaotic approach. The one-hour ahead prediction is carried out for one month period. The correlation coefficient value between the observed and predicted O3 pollution is 0.9165. This excellent result indicates that the local mean approximation method is suitable for predicting O3 pollution and chaotic approach is an appropriate approach which can be applied in analyzing and predicting O3 pollution. These results are expected to assist stakeholders such as the Department of Environment Malaysia, Malaysian Meteorological Department as well as educational institutions for more systematic pollution management.Â